Epidemiological and Clinicopathological Features of Anaplasma phagocytophilum Infection in Dogs: A Systematic Review - El Hamiani Khatat, Sarah; Daminet, Sylvie; Duchateau, Luc; Elhachimi, Latifa; Kachani, Malika; Sahibi, Hamid (Frontiers in Veterinary Science, 2021)
Anaplasma phagocytophilum is a worldwide emerging zoonotic tick-borne pathogen transmitted by Ixodid ticks and naturally maintained in complex and incompletely assessed enzootic cycles. Several studies have demonstrated an extensive genetic variability with variable host tropisms and pathogenicity. However, the relationship between genetic diversity and modified pathogenicity is not yet understood. Because of their proximity to humans, dogs are potential sentinels for the transmission of vector-borne pathogens. Furthermore, the strong molecular similarity between human and canine isolates of A. phagocytophilum in Europe and the USA and the positive association in the distribution of human and canine cases in the USA emphasizes the epidemiological role of dogs. Anaplasma phagocytophilum infects and survives within neutrophils by disregulating neutrophil functions and evading specific immune responses. Moreover, the complex interaction between the bacterium and the infected host immune system contribute to induce inflammatory injuries. Canine granulocytic anaplasmosis is an acute febrile illness characterized by lethargy, inappetence, weight loss and musculoskeletal pain. Hematological and biochemistry profile modifications associated with this disease are unspecific and include thrombocytopenia, anemia, morulae within neutrophils and increased liver enzymes activity. Coinfections with other tick-borne pathogens (TBPs) may occur, especially with Borrelia burgdorferi, complicating the clinical presentation, diagnosis and response to treatment. Although clinical studies have been published in dogs, it remains unclear if several clinical signs and clinicopathological abnormalities can be related to this infection.